R147W in PROC Gene Is a Risk Factor of Thromboembolism in Thai Children - Nongnuch Sirachainan (2018)
© 2017, © The Author(s) 2017. The p.R147W mutation, the c.C6152T in exon 7, causing a change in amino acid from arginine to tryptophan of the PROC gene has been reported as a common mutation in Taiwanese populations with venous thromboembolism (VTE). The present study aimed to identify the prevalence of p.R147W in the Thai population and children with TE and the risk of developing TE. Patients aged ≤18 years diagnosed with TE were enrolled. The PROC gene was amplified by polymerase chain reaction using a specific primer in exon 7. The restriction fragment length polymorphism was designed using MwoI restriction enzyme. A total of 184 patients and 690 controls were enrolled. The most common diagnosis of TE was arterial ischemic stroke (AIS), at 100 (54.3%), followed by VTE, at 38 (20.6%), and cerebral venous sinus thrombosis (CVST), at 23 (12.5%). The prevalence of heterozygous and homozygous p.R147W in patients and controls was 9.5% versus 5.8% and 2.7% versus 0.1%, respectively. Heterozygous p.R147W had odds ratios (ORs) of 1.8 (95% confidence interval [CI]: 1.0-3.2, P =.04), 3.2 (95% CI: 1.2-8.2, P =.009), and 4.5 (95% CI: 1.6-12.8, P =.002) of developing overall TE, VTE, and CVST, respectively. Homozygous p.R147W had ORs of 20.2 (95% CI: 2.3-173.7, P < .001), 21.4 (95% CI: 2.2-207.9, P < .001), and 43.3 (95% CI: 3.8-490.6, P < .001) of developing overall TE, AIS, and CVST, respectively. This study suggested that p.R147W is a common mutation and increased risk of TE in Thai children.